ASSESSMENT OF CLINICAL CHARACTERISTICS OF DEEP PLANTAR WARTS - La Thi Sao Mai,; Trinh Cong Dien,; Nguyen Thi Quynh,; Le Thi Hong Thanh, (Tạp chí Y học Quân sự, 2026)
Objectives: To evaluate the clinical characteristics of patients with deep plantar warts.. Subjects and methods: This was a prospective, descriptive cross-sectional study on 80 patients with deep plantar warts examined and treated at the Outpatient Department and Dermatovenereology Department of Military Hospital 103 (June 2025 - February 2026). Results: The median age was 22 (21-31,5) years. Most patients were male (88.8%). The majority were military personnel (85%). The most common location of lesions was the left foot (46.3%), followed by the right foot (37.5%). The size of the lesions was mainly 2-5 mm in diameter (83.8%, p < 0.001). Most patients had 1-2 papular lesions (63.7%, p < 0.001). Most patients experienced mild pain (82%, p < 0.001). Conclusion: The majority of patients examined were military personnel, male, young, with a small number of lesions (1-2 lesions), 2-5 mm in diameter, and mild pain.